MENINGKATKAN EFEKTIFITAS ANAK USIA DINI MELALUI PERMAINAN EDUKATIF UNTUK MELATIH KONSENTRASI ANAK - Rita Nofianti (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2019)
The development of the world in early childhood is playing. Playing while learning is the world's preconception for early childhood. Early childhood can not be forced to the system of learning, because they are the time of play, so we as teachers organize and conditioned the concept of learning early childhood, and it is certain if we as a teacher of PAUD or TK must Creative to create a fun and rewarding learning process for early childhood developmental phases. Playing educative is one way to improve the effectiveness of early childhood. With educational methods that play the game type is early childhood looking for objects that are friends or their own partner. For example the right socks with the left and spoon with a fork. With very simple playing activities directly, the child's concentration will be more focused and for his or her cognitive development can also be. And for the physical development of the motorist is also included. The goal of this dedication is the PAUD children attending school. Because with the results of the observation team (Chairman) is indeed very early childhood that lack of concentration in the learning process and coupled with bored and half-children in the process of learning activities.